2022
DOI: 10.3389/fonc.2022.899385
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane Protein 100 Inhibits the Progression of Colorectal Cancer by Promoting the Ubiquitin/Proteasome Degradation of HIF-1α

Abstract: Transmembrane protein 100 (TMEM100) is involved in embryonic cardiovascular system development. However, the biological role of TMEM100 in human cancers, particularly colorectal cancer (CRC), is unclear. In this study, tissue microarrays were stained using immunohistochemistry methods to evaluate the association between TMEM100 levels and clinic-pathological features for CRC. Kaplan–Meier and log-rank tests revealed that decreased levels of TMEM100 correlated with shorter overall survival. Cox regression revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…The prognosis for ESCC remains challenging, partially due to the absence of prognostic biomarkers capable of identifying high-risk patients and facilitating the assignment of risk-appropriate monitoring and treatment regimens. TMEM100 is well established as an oncogene, as demonstrated by its inhibitory role in colorectal cancer progression through the promotion of ubiquitin/proteasome degradation of hypoxia-inducible factor-1 alpha[ 22 ]. The downregulation of TMEM100, mediated by histone deacetylase 6, expedites the development and progression of non-small cell lung cancer[ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis for ESCC remains challenging, partially due to the absence of prognostic biomarkers capable of identifying high-risk patients and facilitating the assignment of risk-appropriate monitoring and treatment regimens. TMEM100 is well established as an oncogene, as demonstrated by its inhibitory role in colorectal cancer progression through the promotion of ubiquitin/proteasome degradation of hypoxia-inducible factor-1 alpha[ 22 ]. The downregulation of TMEM100, mediated by histone deacetylase 6, expedites the development and progression of non-small cell lung cancer[ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…UPS dysregulation due to E3-related genes (E3RGs) mutations is strongly associated with poor cancer survival (Seeler and Dejean, 2017). In Colon Cancer pathogenesis, emerging studies have found the critical role of E3-related proteins, such as ZNF280A (Tian et al, 2022, 14), TMEM100 (Zheng et al, 2022), RNF43 (Schatoff et al, 2017;Siraj et al, 2022), and TRIM52 (Guo et al, 2022). Additionally the E3 ligases, RNF128 (Zhuang et al, 2022, 128) and TRIM29 (Jiang et al, 2021) have been reported in the regulation of PI3K/Akt pathway in colorectal cancer.…”
mentioning
confidence: 99%